SAFFRON CULTIVATION TECHNOLOGY - M. A. Mirzayeva (Journals Park Publishing, 2024)
In this article, the spread of the medicinal saffron plant, biological properties, structure, medicine, people in the farm importance, cultivation technology, chemical composition about data given.
Keywords: Medicine property, chemical part , type and category, planting maturity, reproduction, productivity, disease, raw materials, spices, pharmaceuticals, reproduction method.